A tríade ambiental: serviços ecossistêmicos, legislação e conservação na prevenção de desastres naturais - Teixeira, Marcela Ribeiro e Silva (Universidade Federal de São Carlos, 2025)
The predatory development driven by human activities accelerates climate change, which in turn intensifies natural extreme events, further exacerbated by environmental degradation. From the perspective of coastal landscapes, rapid urban growth has compromised the ability of coastal areas to respond effectively to extreme events, significantly increasing their vulnerability. The Santa Catarina coastline is of high tourist interest, which fuels real estate speculation aimed at building condominiums, resorts, and vacation homes, resulting in environmental degradation that significantly impacts Coastal Wetlands. Consequently, there is a reduction in the availability of ecosystem services, leading to economic, social, and environmental losses. This study focuses on diagnosing the coastal landscape of Santa Catarina in relation to flood disasters by using parameters such as topography, soil characteristics, land use and cover, precipitation, and environmental legislation. The research employed a matrix calculation in a GIS environment, overlaying rasterized maps for each parameter. The analyses, which highlight areas of greater hydrological significance and flood susceptibility, emphasize that conserving key areas such as coastal wetlands is essential for providing flood control ecosystem services. However, Brazilian environmental legislation falls short in offering adequate protection for these areas. Thus, rethinking urban development while respecting the conservation of natural areas that ensure the provision of ecosystem services becomes indispensable for public and environmental safety.
The environmental triad: ecosystem services, legislation, and conservation in the prevention of natural disasters
Keywords: Desastre natural; Serviço ecossistêmico; Controle de inundação; SIG; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA